Unraveling the interplay: financial inclusion's impact on growth, trade dynamics, and foreign investment – a comprehensive empirical study - Kushwah, S.V.; Siddiqui, A.A. (University of Jaffna, 2024)
The present study develops a Financial Inclusion (FI) index and extends an interlinkage between FI and Economic Growth (EG). The study is the first to develop an FI index created for the main trading nations from 2001-2019 based on financial development, financial depth, and financial stability and creates an association between FI and EG, including trade and foreign investment. Once the FI index is constructed, panel data analysis is applied by examining the stationarity and cointegration of the series, followed by panel regression and causality tests. Findings highlight a strong interlinkage between FI, EG, trade, and foreign investment for the selected nations. It suggests that the nations emphasize financial inclusion to stimulate EG, enhance trade, and increase foreign investment inflows. Each of the three variables is highly integrated, as indicated in the results, and acts as prerequisites for each other. The study is a significant contribution to the field of FI, trade, and EG. As very few studies have been carried out for integrated analysis, this study helps devise policies for expanding further relationships between FI, trade, investment, and EG across nations. Moreover, this study is the first to select a time period that marks major events like the US-China Trade War (2018) and the Global Financial Crisis (2008). The results of this study are helpful to the governments and policymakers of various economies. They can improvise the existing policies and procedures related to trade and foreign investment to enhance FI and EG. It is seen that for each country, the effect of the variables selected is different. In terms of developing holistic and effective trade policies, each nation can assess the relationship between these four key macroeconomic variables.
Keywords: Economic Growth; Financial Inclusion; Investment; Regression; Principal Component Analysis; Trade Openness